Molecular insights into acetyl triethyl citrate (ATEC) induced toxic effect in HepG2 cells based on multi‐omics integrative analysis - Bing Jie Ma; Lu Chen; Rui Weng; Jia Xi Liu; Xiao Qian Yin; Yu Shun Lu; Jing Qiu; Yong Zhong Qian; Yan Yang Xu (eFood)
Abstract Citrate esters have become the main alternatives to traditional plasticizers in food packaging materials. However, there is a lack of understanding of their toxic effects, particularly the combined effects and inner mechanisms has not been well studied. Our group pioneered the study on combined toxicity of tributyl citrate (TBC) and acetyl triethyl citrate (ATEC), two commonly co‐used citrate esters in food packaging materials. The results showed that exposure to TBC and ATEC can decrease the viability of HepG2 cells in a dose dependent manner. When the mixtures of ATEC and TBC exposed to HepG2 cells, they exhibited antagonism effect. Therefore, ATEC was selected to investigate the molecular mechanisms with multi‐omics techniques at its 1/4 EC50 concentration. A total of 31 metabolites with significant changes were found as potential biomarkers. The LIPG (Lipase G, endothelial type) and GCLM (glutamate‐cysteine ligase modifier subunit) were identified as differentially expressed genes based on transcriptomic analysis. Moreover, downregulated l‐glutamate and l‐glutamine which participate in TCA cycle, resulting in the collapse of energy production and cytotoxicity. These findings on major metabolic pathways will provide insight into the mechanism of cytotoxicity of HepG2 cells after ATEC exposure.